Model dan prototipe inkubator mobile menggunakan kontroler PID berbasis Arduino Uno - Munadi Munadi; R. Andhika Pandu; Rizky Wiradinata; Hari Peni Julianti; Rudy Setiawan (Jurnal Teknologi dan Sistem Komputer, 2020)
One of the causes of the high infant mortality rate in Indonesia is the lack of health support facilities in remote areas, including incubators, to keep the baby's body warm at a specific temperature. This research develops a model and prototype of a mobile incubator to carry and maintain the baby's temperature during emergencies to get further treatment to hospitals that have better facilities than incomplete health clinic facilities. The mobile incubator prototype uses a PID controller system with the optimum gain value Kp 1.501, Ki 0.016, and Kd -1,319 from the results of modeling and tuning in Matlab. The results of the bode plot analysis show that system stability was achieved with a gain margin of 109 dB. The incubator's operational mobility can last up to 59.6 minutes with two 12 V, 5 Ah batteries.